Syntrophic cocultures of Geobacter sulfurreducens and Syntrophobacter fumaroxidans growing on propionate and Fe (III) or a solid electrode as electron acceptors - Mollaei, Monir (2017)
Microbiology Centennial Symposium 2017 - Exploring Microbes for the Quality of Life (Book of Abstracts)